Maternal Mortality: A Review from Eastern Nepal - Rijal, P; Agrawal, A; Pokharel, H; Pradhan, T; Regmi, MC (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to assess the main causes of maternal mortality and other co-morbid factors contributing to maternal death at a university teaching hospital. Methods: A retrospective study was carried out in the department of Obstetrics and Gynecology analyzing all case record of maternal deaths from April 2008 to April 2011. Results: Eclampsia, unsafe abortion, puerperal sepsis, hemorrhages were the leading causes of death. Majority of the patients were unbooked. Conclusions: Eclampsia, sepsis and hemorrhage were the main causes of maternal deaths. Elderly ages, illiterate status, rural residence, presence of prior medical disease were statistically significant factors contributing to maternal death. DOI: http://dx.doi.org/10.3126/njog.v9i1.11185 NJOG 2014 Jan-Jun; 2(1):33-36